Effect of Internal Control System and Reward System on Managerial Performance with Locus of Control as Moderating Variable in Banking - Aditya Halim Perdana Kusuma Putra; E. Elpisah (Golden Ratio of Data in Summary, 2023)
This study aims to: (1) assess the effect of the internal control system on managerial performance, (2) To assess the effect of the reward system on managerial performance (3) assess the effect of the internal control system on managerial performance with the locus of control as a moderating variable; (4) To assess the effect of the reward system on managerial performance with the locus of control as a moderating variable. This study uses primary data through a survey of 36 managers divided into three groups in each pre-determined sub-branch office at Mandiri Bank, Indonesian People's Bank, State Savings Bank, and CIMB Niaga Makassar City. Data were analyzed using the statistical product and service solution (SPSS) program. The results of this study indicate that: (1) the internal control system has a negative and significant effect on managerial performance, (2) the reward system has a positive and significant effect on managerial performance, and (3) the internal control system has a positive and significant effect on managerial performance with a locus of control. as a moderating variable, (4) Reward system has a negative and significant effect on managerial performance with the locus of control as a moderating variable.